Adrenal steroids modulate the phenotype and function of M. tuberculosis-stimulated human dendritic cells - Angerami, Matías (2013)
Cell-mediated immunity, cytokines induced during the specific immune response and T-cell populations are crucial factors for containing Mycobacterium tuberculosis infection. Recent reports suggest a cross-regulation between adrenal steroids (glucocorticoids and dehydroepiandrosterone, DHEA) and the function of antigen-presenting cells (APCs). Therefore, we investigated the role of adrenal hormones on the functional capacity of M. tuberculosis-induced dendritic cells (DCs). Cortisol significantly inhibited the functions of M. tuberculosis-induced DCs. Interestingly, the presence of DHEA enhanced the M. tuberculosis-induced expression of MHC I, MHC II and CD86 and also increased ERK1/2 phosphorylation. Moreover, DHEA improved the production of IL-12 in response to M. tuberculosis stimulation, diminished IL-10 secretion and could not modify TNF-α synthesis. Importantly, we observed that DHEA enhanced the antigen-specific T-cell proliferation and IFN-γ production induced by M. tuberculosis-stimulated DC. These data show for the first time the relevance of the adrenal axis (especially of DHEA) in the modulation of DC function in the context of tuberculosis, a disease where the induction of a Th1 environment by APCs is crucial for the development of an effective immune response to the mycobacteria.